Controllable and observable control design of wind generator system using PID algorithm - Setiawan, B; Riskitasari, S; Putri, R I; Adhisuwignjo, S; Syamsiana, I N; Nurwicaksana, W A (Journal of physics. Conference series, 2019)
This paper describes a design process of the wind generator control system. Controlling a wind generator, fan, is important to study the design of the wind turbine. A complex wind generator model was approximated with 5th order polynomial function. The paper describes a procedure for identifying system, especially for finding the transfer function of a plant, that based on input and output. The plant's input is an electric motor fan voltage and output is wind speed produced. It's important to simplify control's design of the wind generator for configuring transfer functions of the plant. The identification method that is used is Linear Regression, applying Excel program, which produces a polynomial function. And then, the Matlab's System Identification Toolbox (SIT), which produces a transfer function. From this study, applying SIT, a model of wind generator, shows the fit estimation data is 90.78% and MSE is 0.078%. A closed-loop control system using PID controller is proposed. Controllable and Observable of the state space model were verified. The best performance of the close-loop system was achieved using Kp=0.2247, Ki=6.05*10-5, and Kd=208.75 applying Ziegler-Nichols. The results showed that the closed loop stability by applying PID can stabilize the wind generator.